2020
DOI: 10.3390/children7040037
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Mechanism of Adolescents’ Depression: A Dose-Response Relation with Physical Activity

Abstract: Depression has become the most prevalent mental health problem in developing countries, and especially among adolescents. Lubans and his colleagues proposed a psychosocial mechanism to understand the trajectory of mental health (i.e., depression). Thus, this study aimed (1) to examine the relations between different doses of physical activity (PA), light PA (LPA), moderate PA (MPA), and vigorous PA (VPA), academic self-efficacy, and depression among adolescents, and (2) to investigate the direct and indirect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…Those with poor confidence in their capabilities consider difficult tasks as threats, have weak ability to cope with pressure, become stressed or depressed, and display higher probability to give up [ 10 ]. This relation has also been confirmed in the case of adolescents [ 11 , 12 ]. Given these arguments, some scholars consider the perceived self-efficacy as a cognitive precursor of anxiety and depression [ 13 ] as those who do not believe that they are capable to cope with difficult tasks and challenges feel higher levels of anxiety [ 3 ].…”
Section: Introductionsupporting
confidence: 58%
“…Those with poor confidence in their capabilities consider difficult tasks as threats, have weak ability to cope with pressure, become stressed or depressed, and display higher probability to give up [ 10 ]. This relation has also been confirmed in the case of adolescents [ 11 , 12 ]. Given these arguments, some scholars consider the perceived self-efficacy as a cognitive precursor of anxiety and depression [ 13 ] as those who do not believe that they are capable to cope with difficult tasks and challenges feel higher levels of anxiety [ 3 ].…”
Section: Introductionsupporting
confidence: 58%
“…Our study also showed that an additional 60 min/d of PA was associated with a lower risk of psychosomatic complaints, which is in line with earlier research [ 11 , 19 , 20 , 21 ]. Specifically, our study showed that meeting the daily PA recommendations (≥60 min/d) can offer protective effects against psychosomatic complaints for as much as 54% in boys and 41% in girls.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, adolescence represents a per of rapid development and significantly decreased PA participation in this age group w noticed [34][35][36][37]. Increasing numbers of experimental studies also support that increa PA participation may result in a small but positive effect on depression among yo [25,38,39]. Hughes and colleagues [40], for example, found that depressed adolesce (12-18 years) demonstrated a rapid reduction of depression after the 6-8 weeks of intervention, but no significant differences were observed after a 12-week interventi To date, the underlying mechanism of the positive effect of PA on depression has not b investigated.…”
Section: Introductionmentioning
confidence: 99%